Sex differences in amygdala shape: Insights from Turner syndrome. Issue 4 (28th January 2016) - Green, Tamar; Fierro, Kyle C.; Raman, Mira M.; Foland‐Ross, Lara; Hong, David S.; Reiss, Allan L.
Abstract: Objective: Sex differences in the manifestation of psychiatric disorders, including anxiety disorders, are among the most prominent findings in psychiatry. The study of Turner syndrome (TS), caused by X‐monosomy, has the potential to reveal mechanisms that underline male/female differences in neuropsychiatric disorders. The amygdala has been implicated in numerous neuropsychiatric disorders. Previous studies suggest an effect of TS on amygdala volume as well as on amygdala‐related behaviors such as anxiety. Our objective is to investigate the amygdala shape in TS. Specifically, we tested whether amygdala enlargements in TS are localized to specific nuclei implicated in anxiety, such as the basomedial nucleus. Experimental design : We use a surface‐based analytical modeling approach to contrast 41 pre‐estrogen treatment girls with TS (mean age 8.6 ± 2.4) with 34 age‐and sex‐matched typically developing (TD) controls (mean age 8.0 ± 2.8). Anxiety symptoms were assessed using the Revised Children's Manifest Anxiety Scale ‐ 2 (RCMAS‐2) in both groups. Principal observations : TS was associated with anomalous enlargement of the amygdala. Surface‐based modeling revealed shape differences (increased radial‐distances) in bilateral basal and basomedial nuclei within the basolateral complex. RCMAS‐2 Total Anxiety t ‐score was significantly higher in participants with TS compared with TD controls ( P = 0.012). Conclusions: Group differences in global amygdala volumes were driven by local morphological increases in areas that are critically involved in face emotion processing and anxiety. In the context of increased amygdala volumes in TS, our results also showed increased worry and social anxiety in young girls with TS compared with TD. Hum Brain Mapp 37:1593‐1601, 2016 . © 2016 Wiley Periodicals, Inc.